Factors contributing to sodium dodecyl sulphate (SDS) sedimentation in irrigation wheat - Mashamba, Nthabiseng Takalani (University of the Free State, 2017)
The main objective of this study was to determine factors contributing to sodium dodecyl sulphate-sedimentation volume (SDSVOL) in elite wheat breeding lines grown at three different irrigation locations. This was possible through the use of sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE), mixograph analysis and size exclusion-high performance liquid chromatography (SE-HPLC) techniques. Genotype and environment effects were highly significant for SDSVOL, measured quality characteristics as well as the protein fractions, whereas genotype by environment (GxE) interaction was either significant or not significant for most of the measured variables and highly significant for almost all the protein fractions except the absolute value. Relationships between SDSVOL and other quality characteristics varied in combined and single location analysis of variance. The combined analysis shows a positive relationship between SDSVOL and flour protein content (FPC), high molecular weightglutenin subunits (HMW-GS) and dough characteristics. Protein fractions also revealed positive relationships with SDSVOL and the measured characteristics such as FPC, envelope peak integral (EPI), midline right integral (MRI) and envelope peak time (EPT). Principal component analysis (PCA) reduced 21 quality characteristics to five principle components, which explained 99.83% of total variance of envelope tail integral (ETI), midline left integral (MLI), midline peak integral (MPI), MRI, midline tail integral (MTI), SDSVOL and EPI. The SDSVOL and MRI showed the strongest discriminatory power compared to the other measured quality characteristics. Five of the elite lines (13, 12, 7, 2 and 1) can be recommended to breeders for further evaluation based on their good quality characteristics and strong relationship with some measured quality characteristics.
Dissertation (M.Sc.Agric. (Plant Sciences: Plant Breeding))--University of the Free State, 2017
Keywords: Sodium sulfate; Wheat -- Irrigation; SDS-PAGE; Mixograph parameters; Bread making quality; SDSVOL; PCA; SE-HPLC; Wheat -- Breeding